2018
DOI: 10.1038/s41598-018-26241-7
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous cell disruption and semi-quantitative activity assays for high-throughput screening of thermostable L-asparaginases

Abstract: L-asparaginase, which catalyses the hydrolysis of L-asparagine to L-aspartate, has attracted the attention of researchers due to its expanded applications in medicine and the food industry. In this study, a novel thermostable L-asparaginase from Pyrococcus yayanosii CH1 was cloned and over-expressed in Bacillus subtilis 168. To obtain thermostable L-asparaginase mutants with higher activity, a robust high-throughput screening process was developed specifically for thermophilic enzymes. In this process, cell di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 43 publications
2
19
0
13
Order By: Relevance
“…A series of strategies have been used to improve L-asparaginase production, such as optimization of fermentation medium and process [9][10][11], signal peptide screening, promoter mutation, and N-terminal deletion [12]. To date, the highest yield of L-asparaginase obtained was 2168 U/mL, which was reported in our previous work [13].…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…A series of strategies have been used to improve L-asparaginase production, such as optimization of fermentation medium and process [9][10][11], signal peptide screening, promoter mutation, and N-terminal deletion [12]. To date, the highest yield of L-asparaginase obtained was 2168 U/mL, which was reported in our previous work [13].…”
Section: Introductionmentioning
confidence: 68%
“…To further improve the production of L-asparaginase, 300 RBS sequences were designed, and they were divided into 10 groups on average with a gradient of translation initiation rates for statistical convenience. After assaying by the high-throughput screening method developed in our previous study [13], we found most of RBS in the group 1 × 10 3 -2 × 10 3 au, 2 × 10 3 -5 × 10 3 au, 5 × 10 3 -1 × 10 4 au, 1 × 10 4 -5 × 10 4 au, 5 × 10 4 -1 × 10 5 au, 1 × 10 5 -2 × 10 5 au, 2 × 10 5 -5 × 10 5 au, 5 × 10 5 -1 × 10 6 au, 1 × 10 6 -2 × 10 6 au, and 2 × 10 6 -max (5 687 190 au) increased the enzyme activity in the range of 1-1.2%, 2-4%, 4.1-5.2%, 8.8-29.0%, 29.2-51.2%, 51.7-62.1%, 62.5-74.5%, 74.9-81.7%, and 82-96%, respectively (Figure 2). The predicted translation initiation rates and the enzyme activities of most of synthetic RBS were directly proportional.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations